Strategi Dinas Pekerjaan Umum dan Tata Ruang dalam Meningkatkan Ketahanan Pangan di Kecamatan Gunung Halu, Kabupaten Bandung Barat - Ulya, Nurul; Hapsari, Ulfa Siti (Department of Public Administration, Parahyangan Catholic University, 2025)
Food security is one of the important issues in regional development, especially in West Bandung which contributes greatly to food production in West Java Province. Gunung Halu Subdistrict has extensive agricultural land, but its productivity is hindered by an inadequate irrigation system. This study aims to analyze the strategy of the Public Works and Spatial Planning Agency (PUTR) in improving food security, identifying supporting and inhibiting factors, and examining efforts that have been made to overcome obstacles in food security. Jack Kooten’s strategy model (1991:81) was used, which consists organizational strategy, program strategy, resource support strategy, and institutional strategy. This study is qualitative with a phenomenological approach. Data were collected through interviews, observations, and documentation studies. The results of the study indicate that the PUTR has implemented various irrigation development programs to support agricultural productivity in Gunung Halu Subdistrict. However, the challenges faced include the complex geographical conditions of the area and limited community involvement in the management of the irrigation system. Supporting factors for increasing food security include extensive agricultural land and the Development Planning Deliberation (Musrenbang) forum, which functions as a means of reporting if there is damaged irrigation. The PUTR strategies taken include water resource management and optimization of irrigation systems to increase agricultural yields. This research is expected to be a reference for local governments in developing more effective strategies to achieve food security.